PENGARUH PENGELUARAN PEMERINTAH TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI SUMATERA UTARA - , Heston Pero ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aimed to analyze the effect of government spending on economic growth in the Province of North Sumatra by district / city in the year 2008-2012, based implementation Permendagri 59 of 2007 on the budget exists concerning the structure of government spending on indirect expenditures and direct spending also influence labor in the province of North Sumatra. In this study were used to analyze the results of the regression is regression analysis using pool estimate. In the pool estimate regression using three approaches. The first is the common effect approach, and the second approach is the fixed effect and random effect last approach. After that, testing is done using the Chow test, Hausman test and Lagrange Multiplier test (LM) to determine the approach to be chosen. After analysis, the results obtained from the North Sumatra government spending year 2008-2012 that the effect of variable Indirect Expenses (BTL) and direct expenditure (BL) does not show the effect on economic growth in the Province of North Sumatra. For labor variables have a positive influence on economic growth in the Province of North Sumatra. Known to economic growth in North Sumatra increased after experiencing local autonomy. But making a negative influence on the variable less than optimal due to the government of North Sumatra efficiency of government spending. Need to improve the quality of performance and require priority in running the budget policy. Keywords: Economic growth, Indirect spending, Direct spending and Labor